Azadirachta indica A. Juss. (Neem): Reproductive Studies in Relation to Spermidine Application - Sabherwal, Suhani; Dhir, K. K. (Indian Forester, 2010)
The in vivo morpho-physiological responses to spermidine application in Neem (A. indica) were studied during three consecutive annual reproductive flushes from bud development onwards to seed set (prior standardization with endogenous levels). The number of buds and flowers per inflorescence was higher in treated branches as compared to the control. Physiological responses were observed to be polyamine-specific. Year 1 sample protein, total sugar and reducing sugar measured higher following spermidine at 0.2 mM as compared to spermidine at 0.5 mM. The response to year 2 treatments was even better, being significant in 0.2 mM spermidine samples. Year 3 spermidine treatments produced poor flowering response, longer juvenility and low contents of the above compounds as compared to the control. The enzyme assay measuring the activities of invertase, protease, acid- and alkaline phosphatases was consistent with the biochemical responses to the spermidine treatments. In control, a shorter regeneration phase seems to lead to lower productivity in terms of floral inflorescence and fruit set. Therefore, it is suggested that the application of spermidine may regulate the reproductive phase resulting in improved organ/biomolecule production.